Alluvial Soil Physical Properties in A Post-Earthquake Liquefaction Zone in Yogyakarta: Sifat Fisik Tanah Aluvial Pada Zona Likuifaksi Pasca Gempa Bumi Yogyakarta - Karim, Rauf; Nurcholis, Muhammad (Jurnal Ilmu Tanah dan Air, 2025)
Liquefaction is a secondary impact of earthquakes that can cause severe land degradation, including damage to agricultural areas. Bantul Regency experienced liquefaction during the 2006 earthquake, making it prone to further liquefaction, especially in the Jetis subdistrict. This study investigates the physical characteristics of soils prone to liquefaction and examines the correlation between the soil maturity index and liquefaction potential. Sampling points were determined using purposive sampling. The liquefaction potential index value was calculated using qualitative geological techniques at depths of 0–300 cm, yielding values of 28.40 and 18.01 for perennial tree and seasonal crop areas, respectively. Soil samples were collected, and laboratory analyses, including soil particle size, texture, organic matter, maximum moisture content, electrical conductivity (EC), permeability, redox potential (Eh), and plasticity index, were conducted. The results show key characteristics supporting liquefaction potential, including a dominant sand fraction (79.15%), maximum moisture content (88.94%), moderately fast permeability, high EC (0.416 mS/cm), and Eh values indicating aerobic tendency. All soil samples were categorized as physically immature based on the soil maturity index, reflecting weak interparticle bonding and high dispersion when saturated. Regression analysis between the soil maturity index and median grain size (D50) revealed insignificant correlations, with R = -0.56 (R2 = 0.3161) and 0.38 (R2 = 0.145) for perennial and seasonal crop areas, respectively. Visually, quadratic regression yielded R² values of 0.4109 and 0.4226, suggesting a potential nonlinear pattern. These findings indicate that soil maturity index influences liquefaction propensity. Further research is necessary to understand other controlling variables.